Podobieństwo obiektów opisywanych za pomocą struktur drzewiastych - Lula, Paweł (The similarity of objects represented by trees, 2007)
The Extensible Markup Language (XML) belongs to the group of the most important and the most popular tools of contemporary computer science. The XML may be used for the description of object structure and for data gathering. The scope of the XML applications is very wide and it spreads from the problems of gathering and processing multimedia data, through the database solutions, to the designing and implementation of web services. Trees are the most important data structure in XML language. The XML tree consists of nodes and edges. The nodes may include quantitative, qualitative or textual data. The significance of edges may be expressed by weights. The flexibility of the trees causes that they can be considered as a suitable tool for description of complex objects and hierarchical relationships between elements. On the other hand the processing of tree data is very difficult. The calculation of the similarity measure between XML trees is the main issue of the paper. The survey of propositions on that subject may be found in the first part of the article. Next a full procedurę of the calculation of the tree similarity measure is presented. The final remarks and the directions of further investigations are presented in the last part of the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 72-82